228k views
2 votes
FIND THE FIRST DERIVATIVE OF g(x)=√x² + 2x​​

User Janisha
by
5.2k points

1 Answer

3 votes

We are asked to find the first derivative of,


\longrightarrow g(x) = √(x^2+2x)

Here we can write the term
x^2+2x by adding and subtracting 1 as,


x^2+2x = x^2+2x+1-1


x^2+2x = (x+1)^2-1\quad[\because\, x^2+2x+1=(x+1)^2]

Thus,


\longrightarrow g(x) = √((x+1)^2-1)\quad\dots(1)

Now take,


x+1=\sec\theta\quad\dots(2)


x=\sec\theta-1


dx=\sec\theta\tan\theta\, d\theta


(d\theta)/(dx)=(1)/(\sec\theta\tan\theta)\quad\dots(3)

Then (1) becomes,


\longrightarrow g(x) = √(sec^2\theta-1)

We have,


\sec^2\theta-1=\tan^2\theta

So we get,


\longrightarrow g(x) = \tan\theta

Now,


\longrightarrow g'(x) = (d)/(dx)\,[\tan\theta]

By chain rule,


\longrightarrow g'(x) = (d)/(d\theta)\,[\tan\theta]\cdot(d\theta)/(dx)


\longrightarrow g'(x) = \sec^2\theta\cdot(1)/(\sec\theta\tan\theta)\quad\quad\textrm{[From (3)]}


\longrightarrow g'(x) = \sec\theta\cdot(1)/(\tan\theta)


\longrightarrow g'(x)=(1)/(\cos\theta)\cdot(\cos\theta)/(\sin\theta)


\longrightarrow g'(x)=(1)/(\sin\theta)\quad\dots(4)

But we have,


\sin^2\theta+\cos^2\theta=1


\sin\theta=√(1-\cos^2\theta)


\sin\theta=\sqrt{1-(1)/(\sec^2\theta)}


\sin\theta=(√(\sec^2\theta-1))/(\sec\theta)


\sin\theta=(√((x+1)^2-1))/(x+1)\quad\quad\textrm{[From (2)]}


\sin\theta=(√(x^2+2x))/(x+1)

Hence (4) becomes,


\longrightarrow\underline{\underline{g'(x)=(x+1)/(√(x^2+2x))}}

This is the first derivative of the given function.

User Zsolt Szatmari
by
5.5k points